Impacts of stress hyperglycemia ratio on early neurological deterioration and functional outcome after endovascular treatment in patients with acute ischemic stroke - Dai, Zheng; Cao, Haiming; Wang, Feng; Li, Lei; Guo, Hongquan; Zhang, Xiaohao; Jiang, Haichang; Zhu, Juehua; Jiang, Yongjun; Liu, Dezhi; Xu, Gelin (Frontiers in Endocrinology, 2023)
Background and Purpose: Hyperglycemia has been associated with unfavorable outcome of acute ischemic stroke, but this association has not been verified in patients with endovascular thrombectomy treatment. This study aimed to assess the impact of stress hyperglycemia ratio on early neurological deterioration and favorable outcome after thrombectomy in patients with acute ischemic stroke. Methods: Stroke patients with endovascular thrombectomy in two comprehensive centers were enrolled. Early neurological deterioration was defined as ≥4 points increase of National Institutes of Health Stroke Scale (NIHSS) at 24 hours after endovascular procedure. Favorable outcome was defined as modified Rankin Scale (mRS) score of 0-2 at 90 days of stroke onset. Multivariate regression analysis was used to identify the predictors for early neurological deterioration and favorable outcome. Results: Among the 559 enrolled, 74 (13.2%) patients developed early neurological deterioration. The predictors for early neurological deterioration were high stress hyperglycemia ratio at baseline (OR =5.77; 95% CI, 1.878-17.742; P =0.002), symptomatic intracranial hemorrhage (OR =4.90; 95% CI, 2.439-9.835; P <0.001) and high NIHSS score after 24 hours (OR =1.11; 95% CI, 1.071-1.151; P <0.001). The predictors for favorable outcome were stress hyperglycemia ratio (OR =0.196, 95% CI, 0.077-0.502; P =0.001), age (OR =0.942, 95% CI, 0.909-0.977; P =0.001), NIHSS score 24 hours after onset (OR =0.757, 95% CI =0.693-0.827; P <0.001), groin puncture to recanalization time (OR =0.987, 95% CI, 0.975-0.998; P =0.025), poor collateral status before treatment (ASITN/SIR grade 0-3, OR =62.017, 95% CI, 25.920-148.382; P <0.001), successful recanalization (mTICI 2b or 3, OR =7.415, 95% CI, 1.942-28.313; P =0.001). Conclusions: High stress hyperglycemia ratio may be related to early neurological deterioration and unfavorable outcomes after endovascular thrombectomy in patients with acute ischemic stroke.